Bioactive glass selectively promotes cytotoxicity towards giant cell tumor of bone derived neoplastic stromal cells and induces MAPK signalling dependent autophagy - Fellenberg, Jörg; Losch, Sarina; Lehner, Burkhard; Arango-Ospina, Marcela; Boccaccini, Aldo R.; Westhauser, Fabian (Bioactive materials, 2022)
Giant cell tumors of bone (GCTB) are associated with massive bone destructions and high recurrence rates. In a previous study, we observed cytotoxic effects of three different compositions of bioactive glasses (BGs) towards GCTSC but not bone marrow derived stromal cells (BMSC) indicating that BGs represent promising candidates for the development of new therapeutic approaches. In the current study we aimed to investigate the molecular mechanisms that are involved in BG induced cytotoxicity. We observed, that BG treatment was not associated with any signs of apoptosis, but rather led to a strong induction of mitogen activated protein kinases (MAPK) and, as a consequence, upregulation of several transcription factors specifically in GCTSC. Genome wide gene expression profiling further revealed a set of fifteen genes that were exclusively induced in GCTSC or induced significantly stronger in GCTSC compared to BMSC. BG treatment further induced autophagy that was significantly more pronounced in GCTSC compared to BMSC and could be inhibited by MAPK inhibitors. Together with the known osteogenic properties of BGs our findings support the suitability of BGs as therapeutic agents for the treatment of GCTB. However, these data have to be verified under in vivo conditions.